2010
DOI: 10.1111/j.1439-0507.2010.01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of vulvovaginal candidosis in Sfax, Tunisia

Abstract: Vulvovaginal candidosis (VVC) is a common infection of the female genital tract affecting 75% women at least once in their lifetime. The aim of this study was to determine the incidence and potential risk factors associated with VVC and recurrent vulvovaginal candidosis (RVVC). A prospective study of women with vaginitis symptoms was conducted over 2 years in the regional clinic of population and family education in Sfax. A discriminant analysis was used to evaluate the association between the incidence of Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 32 publications
10
49
0
11
Order By: Relevance
“…This genetic diversity of C. glabrata isolates has many consequences for the epidemiology of RVVC. In a previous epidemiological study, we reported that C. glabrata isolates were significantly predominant in cases of RVVC (34 %) versus sporadic VVC (17.5 %) (Amouri et al, 2011). These findings implied that strains with dominant genotypes may be more virulent than others causing sporadic VVC.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This genetic diversity of C. glabrata isolates has many consequences for the epidemiology of RVVC. In a previous epidemiological study, we reported that C. glabrata isolates were significantly predominant in cases of RVVC (34 %) versus sporadic VVC (17.5 %) (Amouri et al, 2011). These findings implied that strains with dominant genotypes may be more virulent than others causing sporadic VVC.…”
Section: Discussionmentioning
confidence: 73%
“…This suggests that recurrent strains (group I and II) do not possess any significant difference in their genotypes from strains that cause one-off episode of vaginitis (group III). The lack of genetic differentiation of the C. albicans population isolated from RVVC patients is in accordance with the fact that the pathogenesis of RVVC can be due to a myriad of risk factors such as previous history of VVC, intrauterine device contraception and non-compliance with therapy (Amouri et al, 2011;Richter et al, 2005). On the other hand, recurrent C. glabrata isolates were genetically divergent (H50.65).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The population of Candida glabrata clinical isolates included in the present study were recovered during an epidemiological survey of antifungal resistance conducted at the Habib Bourguiba University Hospital in Sfax from January 2005 to December 2007 as previously described (Abbes et al, 2011, 2012; Amouri et al, 2011; Sellami et al, 2011). The specimens were isolated from 30 patients with urinary tract infection, vaginal infection or systemic infections.…”
Section: Methodsmentioning
confidence: 99%
“…•50% of initially infected women will experience at least a second episode [5,6,8,10,11,13-15,18,20],[22-25,27,29-33,36-40,44,46,50,51],[53], and…”
Section: Introductionmentioning
confidence: 99%